Phenotypic diversity in patients with lipodystrophy associated with LMNA mutations - Mory, Patricia B. [UNIFESP] (2012)
Objective: Mutations in LMNA have been linked to diverse disorders called laminopathies, which display heterogeneous phenotypes and include diseases affecting muscles, axonal neurons, progeroid syndromes, and lipodystrophies. Among the lipodystrophies, LMNA mutations have been reported most frequently in patients with familial partial lipodystrophy (FPLD) of the Dunnigan variety; however, phenotypic heterogeneity in the pattern of body fat loss has been observed. in this study, we searched for LMNA mutations in patients with various forms of lipodystrophy.Design and methods: We studied 21 unrelated individuals with lipodystrophy. Subjects underwent a complete clinical evaluation and were classified as typical FPLD (n=12), atypical partial lipodystrophy (n=7), or generalized lipodystrophy (n=2). Molecular analysis of LMNA gene, analysis of body fat by dual-energy X-ray absorptiometry, and biochemical measurements were performed.Results: All patients with typical FPLD were found to carry LMNA mutations: seven patients harbored the heterozygous p. R482W (c.1444C>T), two patients harbored the p.R482Q (c.1445G>A), and two individuals harbored the novel heterozygous variant p.N466D (c.1396A>G), all in exon 8. Also, a homozygous p.R584H (c.1751 G>A) mutation in exon 11 was found. Among patients with atypical partial lipodystrophy, two of them were found to have LMNA mutations: a novel heterozygous p.R582C variation (c.1744 C>T) in exon 11 and a heterozygous substitution p.R349W (c.1045COT) in exon 6. Among patients with generalized lipodystrophy, only one harbored LMNA mutation, a heterozygous p.T10I (c.29C>T) in exon 1.Conclusions: We have identified LMNA mutations in phenotypically diverse lipodystrophies. Also, our study broadens the spectrum of LMNA mutations in lipodystrophy.